Natural Dyes from Ornamental Plants as Sensitizers for Dye-Sensitized Solar Cells (DSSCs): A Review on the Structure-Activity Relationships (SARs) between Power Conversion Efficiencies and Chemical Constituents - Nixon, Peter Daniel; Baby, Ruby; Kumar, Nallapaneni Manoj; Ananthi, Nallamuthu (Russian journal of applied chemistry, 2021)
Among the various types of solar cells, the dye-sensitized solar cells (DSSCs) are a type of thin-film solar photovoltaic cells that have been the subject of intense research for over two decades. The DSSCs are being developed using various photosensitizers, both natural and synthetic dyes; however, in recent years, natural dyes use in DSSCs is getting more attention due to the reduced toxicity levels and preparation cost. Apart from these, the simple preparation methodology and manufacturing ease also favour the DSSCs. Though the DSSCs constructed by utilizing natural dyes are becoming popular, the research on dyes extracted from ornamental plants is significantly less. Also, it appears to be critical in plant selection to ensure better power conversion efficiencies as they mainly depend on the chemical constituents present in the dye. Hence, this study aims to review the past works and provide a consolidated decision on plant selection. First, the DSSCs using the natural extracts of various parts of ornamental plants as sensitizers were reported to give better power conversion efficiencies (PCE) than the DSSCs constructed using the extracts of non-ornamental plants. Second, we disused the electrical characteristics and efficiencies of DSSCs constructed using the extracts of ornamental plants. Third, the structure-activity relationships (SARs) of the constituents present in the extracted dyes of ornamental plants with respect to the overall PCE of the fabricated DSSCs is discussed in detail. Overall, this article provides an in-depth review of 50 plus ornamental plants for DSSC construction.